Observation of strato-mesospheric CO above Kiruna with ground-based microwave radiometry – retrieval and satellite comparison - Hoffmann, C. G.; Raffalski, U.; Palm, M.; Funke, B.; Golchert, S. H. W.; Hochschild, G.; Notholt, J. (Atmospheric Measurement Techniques, 2011)
CO serves as a tracer for dynamics in the polar winter middle atmosphere. This work presents the retrieval and the characterization of ground-based CO measurements from the winters 2008/2009 and 2009/2010 by the Kiruna microwave radiometer KIMRA, located in northern Sweden (67.8° N, 20.4° E). Furthermore, the dataset is used for an extensive comparison to the recent satellite instruments MLS on Aura, ACE-FTS, and MIPAS on Envisat. The vmr profiles are retrieved using the optimal estimation approach. A detailed analysis of the averaging kernel functions is carried out, showing sensitivity of the measurements between 40 and 80 km altitude, a vertical resolution of 16 to 22 km, as well as a residual influence of the region up to 130 km altitude. An error assessment reveals a total error of the retrieved profile that increases with altitude and is approx. ±0.1 ppmv at 50 km altitude and ±3 ppmv at 80 km altitude. The main contributions to this total error arise from the measurement noise and the uncertainty of the used temperature profiles. The expected dynamical features of the polar winter middle atmosphere are qualitatively identified in the retrieved time series, but are not quantitatively analyzed here. The dense MLS dataset is used to investigate the influence of the collocation criteria on the satellite comparison, showing that relaxing the distance criterion causes a high bias for MLS. The comparison including the other instruments is difficult because of the small number of coincidences. However, it suggests that there is a general agreement between KIMRA and the satellite instruments below 65 km altitude, but a high bias for KIMRA above this altitude. Furthermore, the shape of the KIMRA profile appears to be systematically different from the satellite profiles.